Growth Not Gotcha: The Power of Feedback for Future-Readiness of Teacher Candidates - Kelly Gillespie; Sue Jenkins; Vickie Schweinler (The Advocate, 2017)
Feedback is powerful. Everybody needs feedback. The need for feedback includes teachers. It’s time to transform delivery of instruction and teacher-education with a powerful, 2-step observation-feedback process. Clarity of expectations set the stage for observation. Feedback is delivered instantaneously and regularly. Actionable feedback gets results including growth from self-reflection, collaborative conversation, and differentiated professional learning. Self-efficacy of teacher candidates soars and retention in the profession finally has a fighting chance. Feedback, the breakfast of champions (Blanchard, 2015) gives teachers dollops (Marzano, 2007). Feedback, the missing piece in continuous improvement (Feldman, 2016) and preparation of future-ready teacher candidates.